Food Tourism Revisited - Kunwar, Ramesh Raj (Journal of Tourism and Hospitality Education, 2017)
Though food is the basic need of human being, it is the best way to express the culture and the tradition of a community. Food as a tangible part of cultural and traditional representation attracts most of tourists around the world. Food is one of the important pulling factors while selecting the destination. Though after information revolutions most of the facilities are at a click distance, food is the only one that needs the distance to be covered in order to discover the majestic taste in the native structure. Food majorly  describes the patterns that communities are residing. Most of the native cuisine that attracts most of the foreigners is based on the native resources and way of preparing and presenting foods. In some countries food is not only taken as a means to generate income but also a means to protect their tourism.Journal of Tourism and Hospitality EducationVol. 7, 2017, Page: 83-124